2004
DOI: 10.1074/jbc.m310839200
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for West Nile Virus (–)- and (+)-Strand Subgenomic RNA Synthesis in Vitro by the Viral RNA-dependent RNA Polymerase Expressed in Escherichia coli

Abstract: West Nile virus (WNV), 1 a mosquito-borne member of Flaviviridae family that consists of more than 70 human pathogens, was first isolated in 1937 from the blood of a female patient in the West Nile district of Uganda (1). Since then, the virus has been isolated in humans, birds, and bird-feeding mosquitoes, Culex univittatus. Serological studies revealed a broad distribution of the virus in Africa, West Asia including India, and the Middle East, but only occasionally isolated in Europe, and is thought to be sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 58 publications
5
49
1
Order By: Relevance
“…It has been previously proposed that the 5Ј-3Ј hybridized complementary sequences present in the DV genome constituted the promoter for RNA synthesis (Ackermann and Padmanabhan 2001; You et al 2001;Nomaguchi et al 2004;Alvarez et al 2005b). Here, we demonstrated that these sequences do not promote viral RNA synthesis per se and that the RNA element responsible for this activity is the SLA structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously proposed that the 5Ј-3Ј hybridized complementary sequences present in the DV genome constituted the promoter for RNA synthesis (Ackermann and Padmanabhan 2001; You et al 2001;Nomaguchi et al 2004;Alvarez et al 2005b). Here, we demonstrated that these sequences do not promote viral RNA synthesis per se and that the RNA element responsible for this activity is the SLA structure.…”
Section: Discussionmentioning
confidence: 99%
“…1C). We used a well-characterized assay in which templatelength RNA products of negative polarity were demonstrated for DV RdRp activity (Ackermann and Padmanabhan 2001;Nomaguchi et al 2004). We found that substitutions of specific nucleotides within SLB or 5ЈCS yielded RNAs that were very active as templates (MSLB and MCS RNAs).…”
Section: An Rna Element Present At the 5ј End Of DV Genome Promotes Smentioning
confidence: 99%
See 1 more Smart Citation
“…NS5 comprises an N-terminal methyltransferase (MTase) domain that catalyses both guanine N-7 and ribose 29-O methylations during viral RNA cap formation (Zhou et al, 2007) and a C-terminal domain that harbours the RNA-dependent RNA polymerase (RdRp) (Tan et al, 1996;Guyatt et al, 2001;Nomaguchi et al, 2004;Selisko et al, 2006). The crystal structure of the WNV RdRp revealed classic RdRp structure bearing palm, thumb and finger subdomains (Malet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are two pairs of conserved sequences (59CS1, 39CS1, 59UAR and 39UAR) that together induce DENV cyclization (Alvarez et al, 2005a, b; Hahn et al, 1987). These motifs are essential for negativestrand RNA synthesis of DENV (Ackermann & Padmanabhan, 2001; Alvarez et al, 2005a, b;Villordo & Gamarnik, 2009;You & Padmanabhan, 1999) and other flaviviruses (Bredenbeek et al, 2003;Corver et al, 2003;Jones et al, 2005;Khromykh et al, 2001;Lo et al, 2003;Nomaguchi et al, 2004). On the other hand, sequences present within a large stem-loop structure located at the 59 end as well as a conserved oligo(U) track function as the promoter for viral polymerase activity (Lodeiro et al, 2009).…”
Section: Introductionmentioning
confidence: 99%